Need Assessment of Women Dairy Farmers - Kumari, Saroj; Sethi, Nishi; Malik, Joginder Singh; Yogi, Vikram (Indian Journal of Extension Education, 2015)
The present study was conducted in Hisar district of Haryana state. From Hisar district, two blocks Adampur and Hisar-I  were selected randomly. From selected blocks, two villages, namely Siswal from Adampur and Dabra from Hisar-1 were  selected by random technique. From each selected village, 50 women were selected randomly, thus making a total sample  of 100 women. From selected villages, 20 women who were interested in training in dairy farming were selected  purposively. Majority of the respondents belonged to middle age group, illiterate, married and belonged to joint family of  medium family size. Eighty-four per cent respondents had no social participation and had small herd size. Most of the  respondents (25%) had medium land holding and lived in pacca houses. Training need score was obtained highest for the  task housing management of cattle shed (Mean-76.83 and rank-I), followed by animal health, watering, wallowing and  bathing, breeding, post-parturition care, bedding, care and management of calves, feeding, marketing, farm management  and accounting and milking and milk product preparation ranked from II to XI, respectively. Similarly, training need was  high for animal health (ranked-II) but dairy farm women had high knowledge (74.1) and low difficulty (2.19). It was  surprise to see that after computing frequency, importance, difficulty and knowledge of last ranks were given to farm  management and accounting (X rank) and milking and milk product preparation (XI rank) but highest learning difficulty  by dairy farm women was perceived for these components. It was also interesting to note that negligible percentage of  respondents performed tasks of dairy farm management and accounting and marketing where money matters were  involved.
Keywords: Dairy farming; respondents; women